2020
DOI: 10.3390/nano10030591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structure of Polymers Grafted from Graphene Oxide on the Compatibility of Particles with a Silicone-Based Environment and the Stimuli-Responsive Capabilities of Their Composites

Abstract: This study reports the utilization of controlled radical polymerization as a tool for controlling the stimuli-responsive capabilities of graphene oxide (GO) based hybrid systems. Various polymer brushes with controlled molecular weight and narrow molecular weight distribution were grafted from the GO surface by surface-initiated atom transfer radical polymerization (SI-ATRP). The modification of GO with poly(n-butyl methacrylate) (PBMA), poly(glycidyl methacrylate) (PGMA), poly(trimethylsilyloxyethyl methacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Grafting polymers on modified graphene sheets results in nanocomposites presenting a combination of properties resulting from both materials, namely improved solubility and interfacial energy alternations [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The reaction between polymers and graphene oxide nanosheets involves two methods and specifically the “ grafting from ” [ 17 ], where the GO–initiator complex is primarily prepared in order to initiate the polymerization from the GO surface, and the “ grafting to ” [ 18 ], where the polymeric precursor bearing a functional group reacts with the chemically modified GO [ 19 , 20 , 21 , 22 , 23 ]. Employing the “ grafting to ” method, better control over the polymer’s molecular characteristics can be realized and satisfactory dispersity, and solubility are achieved, while the “ grafting from ” method results in higher coupling yields, but limited control over the molecular characteristics is reported [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grafting polymers on modified graphene sheets results in nanocomposites presenting a combination of properties resulting from both materials, namely improved solubility and interfacial energy alternations [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The reaction between polymers and graphene oxide nanosheets involves two methods and specifically the “ grafting from ” [ 17 ], where the GO–initiator complex is primarily prepared in order to initiate the polymerization from the GO surface, and the “ grafting to ” [ 18 ], where the polymeric precursor bearing a functional group reacts with the chemically modified GO [ 19 , 20 , 21 , 22 , 23 ]. Employing the “ grafting to ” method, better control over the polymer’s molecular characteristics can be realized and satisfactory dispersity, and solubility are achieved, while the “ grafting from ” method results in higher coupling yields, but limited control over the molecular characteristics is reported [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kutalkova et al [ 80 ] prepared two kinds of GO/PHEMATMS composites with different molar masses by the SI-ATRP method, as shown in Figure 4 , and proved that the relaxation time and dielectric polarization strength of the composites had a direct influence on the ER effect. Zygo et al [ 81 ] also prepared four kinds of composite ER materials, GO/PMMA, GO/PBMA, GO/PGMA, and GO/PHEMATMS, and all of them showed improved ER effect. It was also found that GO/PHEMATMS, which is similar to silicon-based environment, showed the best suspension stability and ER effect, where the yield stress is neat GO < PMMA < PBMA < PGMA < PHEMATMS.…”
Section: Go-based Er Fluidsmentioning
confidence: 99%
“…In agreement with the listed literature sources above, the compatibility of the particles and PVDF matrix seems to be crucial. In this respect the modification of the GO particles with various polymers was already developed by our group, when enhanced compatibility was obtained by grafting of poly(methyl methacrylate), poly(butyl methacrylate), poly(styrene), poly(glycidyl methacrylate) and finally, poly(trimethylsilyloxyethyl methacrylate) [ 50 , 51 , 52 ], and thus their stimuli-responsive capabilities were significantly improved. Moreover, such approach provides a considerably softer and more flexible composite than observed for composites consisting of neat particles [ 53 ].…”
Section: Introductionmentioning
confidence: 99%